Tawakal Dalam Perspektif Islam - Achmad . (STAI Syaichona Moh. Cholil Bangkalan, 2019)
Man was created by God as a perfect being because he was blessed with reason so that he can distinguish between good and bad, haq and inner. There are two things that cannot be released in human life, namely endeavor and trust. Efforts are to try and do, not be silent, also not fatalistic. His conviction is quite strong and stable, while trust is an attitude of a servant who is the result of his unanimous belief in God, because he believes that only God created everything, his knowledge is extensive, he is the one who governs and controls the universe. It is this belief that drives him to surrender all his problems to God. His heart is calm and peaceful and there is no suspicion, because Allah is Omniscient and Wise, and there are still many versions of scholars in interpreting tawakal. There are 4 things that must be known in trust, namely: the meaning of trust, the degree of trust, trust in benefits, and characteristics of trust. By knowing the four points of trust, a person can strengthen himself to put his trust in God.